The Influence of Participation on Farmer Group Performance in Sungai Kakap District - Melisarah, Endah; Kurniati, Dewi; Sawerah, Siti (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2026)
A farmer group functions as a platform for local farmers to collaborate, learn, and support each other in agricultural activities. Active participation of farmer group members in various group activities not only strengthens solidarity but also has the potential to improve the group's performance. This study explores the influence of farmer group member participation on group performance in Sungai Kakap District, focusing on Parit Keladi Village. The study population consists of 569 farmers. The sample size was calculated using the Slovin formula, resulting in 123 respondents selected through a multistage sampling technique. The analytical method used is SEM-PLS. This study is distinctive for its comprehensive application of Cohen and Uphoff’s four-dimensional participation framework to Indonesian farmer groups through the SEM-PLS approach, a method rarely employed in this field. The results show that participation in decision-making, implementation, and benefit utilization significantly enhances group performance, while participation in evaluation has no notable effect. This uneven influence across dimensions extends Cohen and Uphoff’s theory by demonstrating that participation is not a uniform process; instead, certain stages contribute more substantially to institutional effectiveness within the Indonesian farmer group context. The findings thus refine the theoretical understanding of participatory dynamics and provide practical insights for strengthening collaboration, improving performance, and promoting the sustainability of farmer groups